Law, Property, and the Individual: A Critical Reassessment - Quoc, Nguyen Anh; Y, Nguyen Van (Prophetic Law Review, 2026)
This article examines the relationship between law, property rights, and the individual in modern society, with a focus on the tension between individual freedom and power, as well as the monetary and social normative mechanisms that shape these relationships. The goal of the study is to clarify how legal and property institutions both protect and limit individual freedom, and to show the corrupting consequences of individuals being made the means of these systems. The method used is qualitative, combining analysis and synthesis, comparison, and the method of reversing pairs of categories (subject–product, means–purpose, inevitability–freedom). This subject becomes a product, a means to an end, and, to that extent, ultimately free. The research demonstrates that a person can be explained not only as a subject, independent of property, but also as a product of power, norms, and money; and that the current law, which regulates property relations, does not yet address the root of social inequality. The significance of this research is to propose repositioning the theoretical foundations of the law, making them more closely linked to the truth of personal life and social responsibility, thereby opening up a new approach to legal science and interdisciplinary research on freedom, fairness, and human dignity.